(untitled) (Annals of Medical Research, 2024)
Aim: Temporal lobe epilepsy surgery is the most common type of epilepsy surgery. This study evaluates the relationship between preoperative auras and surgical prognosis. Materials and Methods: The follow-up data of 100 patients who underwent anterior temporal lobectomy surgery after 2 years was reviewed. The patients were divided into two groups based on the presence or absence of abdominal-emotional (AE) aura. Each patient was evaluated with a detailed history, video-electroencephalography (EEG), neuroimaging, and postsurgical outcomes according to Engel classification to predict postsurgical seizure freedom. Results: After 2 years of follow-up, 71 patients were seizure-free. Based on aura types, univariate analysis showed that the age of disease onset and history of febrile convulsion were higher in the AE (+) group (p=0.013, p<0.001). Additionally, MTS was more frequently observed in the MRI, MRS, and pathology results (p= <0.001, p=0.01, p=0.009). No correlation was found between the presence or type of aura and postoperative seizure-free state. Conclusion: Our results showed that the presence or type of aura had no prognostic significance for seizure freedom after TLE surgery. However, further studies with larger patient numbers are needed to confirm these findings.